2021
DOI: 10.1155/2021/5536793
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age and Breed on Carcass and Meat Quality Characteristics of Beni-Guil and Ouled-Djellal Sheep Breeds

Abstract: Two hundred eight sheep, belonging to two main breeds of eastern Morocco, “Beni-Guil” and “Ouled-Djellal,” were investigated for carcass traits and meat quality. The objective of this study is to determine the effects of breed and age at slaughter on carcass traits and meat quality. The animals were slaughtered at three age classes: milk teeth, animals with two adult teeth, and adult animals. Dressing percentage, carcass measurements, compactness indices, carcass shrinkage parameter, conformation scores, fatne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…and Al-Hamdani for the weight of the neck 1.51, 1.27, 1.79 kg respectively the average weight of the mechanism 2.15, 1.71, 2.38 kg respectively and the average weight of the ribs 4.92 , 4.90, 5.50 kg respectively. These results are close to the results of [8], and agree with the results of [9], as for the characteristics of the weights of the ribs, shoulder and cotton region, the strain did not notice a significant effect on them, and their averages were respectively 2.30, 1.97, 2.48 kg for the ribs and 4.81, 4.76, 4.97 kg for the shoulder and 1.55, 1.50 and 1.65 kg for the cotton area.This result confirmed the results of [16] in their study on the local and Turkish Awassi sheep breeds, where no significant differences were recorded between the breeds in rib and shoulder weight, and contrary to the results of [17], in their study on the Shera and Assaf breeds. The reasons for such differences between the studies are mainly due to the different weights of the lambs included in the experiment and the feeding and weaning systems, as well as the difference in the accuracy of the estimate caused by the method and location of the cutting [18].…”
Section: Effect Of Breed On Some Carcass Cutssupporting
confidence: 93%
See 1 more Smart Citation
“…and Al-Hamdani for the weight of the neck 1.51, 1.27, 1.79 kg respectively the average weight of the mechanism 2.15, 1.71, 2.38 kg respectively and the average weight of the ribs 4.92 , 4.90, 5.50 kg respectively. These results are close to the results of [8], and agree with the results of [9], as for the characteristics of the weights of the ribs, shoulder and cotton region, the strain did not notice a significant effect on them, and their averages were respectively 2.30, 1.97, 2.48 kg for the ribs and 4.81, 4.76, 4.97 kg for the shoulder and 1.55, 1.50 and 1.65 kg for the cotton area.This result confirmed the results of [16] in their study on the local and Turkish Awassi sheep breeds, where no significant differences were recorded between the breeds in rib and shoulder weight, and contrary to the results of [17], in their study on the Shera and Assaf breeds. The reasons for such differences between the studies are mainly due to the different weights of the lambs included in the experiment and the feeding and weaning systems, as well as the difference in the accuracy of the estimate caused by the method and location of the cutting [18].…”
Section: Effect Of Breed On Some Carcass Cutssupporting
confidence: 93%
“…Several studies were conducted to find out the traits of the local sheep carcasses, including the study of [7], and study [8], on Arab lambs reared in the province of Basra the average weight of the carcass was 15.19 kg, and the weight of the head, legs and skin was 2.36, 0.91, 4.67 kg, respectively, while the weights of the pieces were 0.88, 4.64, 2.01, 1.05, 4.74, 1.83 kg for the neck, shoulders, ribs, loins, thighs, and buttocks, respectively. In a study conducted on two breeds of sheep in the Maghreb, it was noted that the Awlad Jalal breed was superior to the Bani Jil breed in carcass weight and some cuts [9]. As for the study of [10], on the Awassi and Kurdish breeds, the percentages of weights of the neck, shoulder, ribs, and cotton region were 3.77, 25.9, 6.11, 9.82% respectively, of the carcass weight of the Awassi sheep, and 3.61 , 25.89, 5.62, 9.84 % respectively, of the Kurdish sheep.…”
Section: Introductionmentioning
confidence: 99%
“…In their study in the spring, the differences due to the slaughter age were observed for the proportions of shoulder and leg, which were greater (p< 0.01) in 60-day and 45-day lambs, respectively. The carcass measures and compactness indexes increased with higher slaughter weight and breed and age at slaughter had a significant effect on carcass traits (p<0.001) (Belhaj et al 2021) which was similar to the current study. With increased live weight at slaughter the percentage of neck, back and rib with flank increased and chuck, shoulder and hindleg decreased according to There were found positive significant interaction of lamb type and slaughter ages among leg, neck, shoulder, rack, & loin and pluck wt%, respectively.…”
Section: Comparison Of Carcass Traits For Edible Part (On Live Weight...supporting
confidence: 90%
“…In ruminants, the evolution of meat quality attributes like color, cooking loss, and textural properties are affected by different production systems (Gonzales-Barron et al, 2021b). In the meat sector, slaughtering age is an important criterion for carcass grading or classification (Belhaj et al, 2021;Dlamini et al, 2020). In the current scenario of the Pakistani meat industry, the overall carcass classification is based on age, sex, weight, and conformation.…”
Section: Effect Of Age On Meat Qualitymentioning
confidence: 99%